2021
DOI: 10.3390/su13010389
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of an Electric Chiller Integrated with a Large District Cooling Plant

Abstract: District cooling (DC) systems have recently proven to be more economically and environmentally viable as compared to conventional cooling techniques. In most DC setups, electric centrifugal chillers (ECCs) are installed to provide chilled water (CW) to charge the thermal energy storage (TES) tank or for direct CW supply to the DC network. The operation of these ECC systems consumes most of the electrical power supplied to the entire DC plant; this therefore strengthens the need to conduct a comprehensive envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The reason for its omission in this research was mainly the lack of data in the Ecoinvent database, or rather the different way of working with the data compared to the building materials. Many studies can be found in the literature that use the Ecoinvent database to calculate the environmental impacts of HVAC systems including the material production phase [47,48], and the authors of this paper have also addressed this topic previously [49]. Linking environmental data with budgeting data for HVAC systems is realistic, but the methods will be very different from those for building materials and will be addressed in future research.…”
Section: General Part Of the Methodsmentioning
confidence: 99%
“…The reason for its omission in this research was mainly the lack of data in the Ecoinvent database, or rather the different way of working with the data compared to the building materials. Many studies can be found in the literature that use the Ecoinvent database to calculate the environmental impacts of HVAC systems including the material production phase [47,48], and the authors of this paper have also addressed this topic previously [49]. Linking environmental data with budgeting data for HVAC systems is realistic, but the methods will be very different from those for building materials and will be addressed in future research.…”
Section: General Part Of the Methodsmentioning
confidence: 99%
“…Furthermore, Salim et al (2019) posit that the ability to offer integrated solutions is a critical capability, as it enables the provision of reliable and rapid responses to changing competitive and environmental landscapes through offering unique solutions at a lower cost and minimum environmental harm. Similarly, Potter and Graham (2019) as well as Huaccho Huatuco et al (2020) concurred that integrating critical stakeholders such as suppliers in solution design enhanced the potential to derive positive outcomes from eco-innovation implementations, particularly as integrated product-service solutions reduced the environmental impact generated across the value creation process and through its life cycle (Hampo et al , 2021). Existing eco-innovation literature has primarily focused on manufacturing sector, and few research articles have focused on eco-innovation application toward other sectors that feature service aspects (Munodawafa and Johl, 2019).…”
Section: Literature Reviewmentioning
confidence: 98%
“…(2020) concurred that integrating critical stakeholders such as suppliers in solution design enhanced the potential to derive positive outcomes from eco-innovation implementations, particularly as integrated product-service solutions reduced the environmental impact generated across the value creation process and through its life cycle (Hampo et al, 2021). Existing eco-innovation literature has primarily focused on manufacturing sector, and few research articles have focused on eco-innovation application toward other sectors that feature service aspects (Munodawafa and Johl, 2019).…”
Section: Literature Review 21 Concept Of Eco-innovation Capabilitiesmentioning
confidence: 99%
“…In various DC facilities, thermal energy storage (TES) systems have been installed to optimize the operation of DC plants and meet the fluctuating demand for the supply of chilled water for air conditioning purposes. Although the vapor compression chiller (VCC) accounts for about 40% of the total electricity supplied to the DC plant [5], studies have shown that integrating the functionalities of VCC and TES into the DC plant leads to a 35% reduction in electricity consumption, compared to conventional DC systems without TES. Different electricity tariffs during various times of the day benefit the integration of TES technology.…”
Section: Introductionmentioning
confidence: 99%
“…Hampo et al [5] used a gate to gate LCA methodology to analyze the environmental performance of four electric chillers. The authors investigated the environmental performance of the chiller systems based on the composition of the 2020 Malaysia's fuel mix and the proposed optimized electricity mix by 2030.…”
Section: Introductionmentioning
confidence: 99%